ASEAN Vision 2020: The Implementation of Cooperation on Food Security (Department of International Relations, Universitas Brawijaya, 2022)
This paper examines the implementation of the ASEAN Vision 2020 in cooperation on food security. The ASEAN Vision 2020 stated that ASEAN will strengthen their cooperation to enhance food security and international competitiveness of food, agricultural and forest products, to make ASEAN a leading producer of these products, and promote the forestry sector as a model in forest management, conservation and sustainable development. ASEAN had built a well-established framework of cooperation on food security. The establishment of the ASEAN Food Security Information System (AFSIS) was praised as an ASEAN achievement in enhancing the cooperation in food security. Although, compared to the objectives of regional economic cooperation and military security mechanism, the objective in strengthening the cooperation on food security remains less significant within the ASEAN's discussions. The question is then, by conducting numerous frameworks of cooperation, did ASEAN excel to achieve the objectives in ASEAN Vision 2020 in the sphere of food security? This paper argues that ASEAN had successfully delivered some positive achievements in the scope of regional cooperation in food security areas. However, to some extent, some ASEAN state-members are still struggling with problems related to food security, particularly regarding food accessibility. The ASEAN growing market brings about a challenge for food supply and greater pressure for the association to ensure environmental sustainability in the region. Regarding its goals within the scope of ASEAN Vision 2020, the association mostly focused on how to achieve their deeper economic integration. In the area of food security, ASEAN has managed to set up a foundation for further regional cooperation under the framework of the ASEAN Community Vision 2025 and ASEAN Vision 2040.